Design and Optimization for Straw Treatment Device Using Discrete Element Method (DEM) - Shaochuan Li; Peisong Diao; Xianghao Li; Yongli Zhao; Hongda Zhao (Agriculture)
Due to the dense crop residue in the Huang-Huai-Hai region, challenges such as large resistance, increased power consumption, and straw backfilling arise in the process of no-till seeding under the high-speed operations. This paper presents the design of a straw treatment device to address these issues. The cutting edge of a straw-cutting disc is optimized using an involute curve, and the key structural parameters of the device are designed by analyzing the process of stubble cutting and clearing. In this study, the Discrete Element Method (DEM) was employed to construct models of compacted soil and hollow, flexible wheat straw, forming the foundation for a comprehensive interaction model between the tool, soil, and straw. Key experimental variables, including working speed, rotation speed, and installation centre distance, were selected. The power consumption of the straw-cutting disc (PCD) and the straw-clearing rate (SCR) were used as evaluation metrics. Response surface methodology was applied to develop regression models linking the experimental factors with the evaluation indexes using Design-Expert 12 software. Statistical significance was assessed through ANOVA (p < 0.05), and factor interactions were analyzed via response surface analysis. The optimal operational parameters were found to be a working speed of 14 km/h, a rotation speed of 339.2 rpm, and an installation centre distance of 100 cm. Simulation results closely matched the predicted values, with errors of 1.59% for SCR and 9.68% for PCD. Field validation showed an SCR of 86.12%, improved machine passability, and favourable seedling emergence. This research provides valuable insights for further parameter optimization and component development.